PENGARUH PROMOSI, KUALITAS PRODUK, DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PADA HOLLAND BAKERY BATAM - Sitorus, Jaya Ricardo; Heryenzus, Heryenzus (SCIENTIA JOURNAL, 2020)
Sales are very important in the activities of a company, then what must be prioritized in increasing company sales is Promotion, Product Quality, Packaging and Purchasing Decisions. in this study the sample used as many as from the total population of 43,463 were as many as 269 respondents and by using the sampling technique used in this study was nonprobability sampling consisting porpive sampling. Determination test results explain that the results of the R Square value of 63.8% the remaining 36.2% are influenced by other variables not in this study, it can be concluded that the independent variables (Promotion X1, Product Quality X2, and X3 packaging) simultaneously affect the dependent variable dependent (purchase decision Y), which is 63.8% positive. Data analysis is used through the results of the t test and f test to find out how much influence between the independent variables on the dependent variable. In this study using SPSS version 20.